2013
DOI: 10.13005/ojc/290338
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Study Intramolecular Hydrogen Bond in Acetylacetone 3- substituted Derivatives: NMR, NBO analysis and Thermo-chemical Investigation

Abstract: The strength of the O-H···O hydrogen bridge in acetylacetone (AA) and acetylacetone derivatives is depending on the nature and size of the substitute groups and on the substitution position. We investigated the effect of electron-pull and electron-donor substitute on the formation of intramolecular hydrogen bonding at 3-substituted acetylacetone derivatives such as nitroacetylacetone (NAA) and methylacetylacetone (MAA). In this research NAA and MAA structures were fully optimized with B3LYP/6-31G*, 6-31G** and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…This finding was different with previous results of Salen‐Fe counterpart where chlorinated substituent group made the central Fe more electron‐deficient and facilitated the reactivity . To explain this difference, an analog computation of Mullikan and NBO charge distribution of 7 a and 8 a were carried out (Figure ) ,,,,. The electrostatic potential diagram (Figure a) showed that the chlorinated substituent on the benzene ring captured the charge on the amine bridge, but the Mullikan charge values (Figure S10) indicated that the chlorine atom as an electron withdrawing group did not show much influence on the central metal atom, instead, made the charge originally concentrated near the axial chlorine more dispersed.…”
Section: Resultsmentioning
confidence: 58%
“…This finding was different with previous results of Salen‐Fe counterpart where chlorinated substituent group made the central Fe more electron‐deficient and facilitated the reactivity . To explain this difference, an analog computation of Mullikan and NBO charge distribution of 7 a and 8 a were carried out (Figure ) ,,,,. The electrostatic potential diagram (Figure a) showed that the chlorinated substituent on the benzene ring captured the charge on the amine bridge, but the Mullikan charge values (Figure S10) indicated that the chlorine atom as an electron withdrawing group did not show much influence on the central metal atom, instead, made the charge originally concentrated near the axial chlorine more dispersed.…”
Section: Resultsmentioning
confidence: 58%
“…The compounds show diverse conformational and stabilized by intramolecular hydrogen bond (HB) [4]. The strength of intramolecular HBs and electronic properties are depending on the nature, size and position of the substituent groups [5]. N-benzoyl-N'-phenylthiourea derivatives stabilized by intramolecular HB (O … H-N) that form pseudo-six membered ring.…”
Section: Introductionmentioning
confidence: 99%